Ma-hā-gu-ruʼi smon lam bźugs so - Padma-gliṅ-pa, Gter-ston, b. 1450? (s.n., 1972)
Prayer (Praṇidhāna) for the spiritual guidance of Padma Sambhava through all one's rebirths; a "rediscovered" teaching of the Nyingmapa sect of Tibetan Lamaism.